الضّغوط النّفسية وعلاقتها بالتّوافق الزّواجي لدى الممرّضات _ دراسة ميدانية بمستشفيات مدينة المسيلة _ - صليحة, عزة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
The current study aimed to identify if there is a correlation statistically significant relationship between psychological stresses and marital adjustment for Nurses working in M sila city hospitals, as well as to identify the level of each of psychological stress and marital adjustment, and to search if there are statistically significant differences in the variables of the study were attributed to (geographical location and work suite and Expience) To achieve these aims the researcheris rely on the descriptive method, and he select a simple random sample consists of (79) nurse which is equivalent to (25 % ) of the original population, to realise the objectives we use the marital adjustment and the psychological stress afteramended it , and after confirmation of their credibility andReliability, we analysis data through using the statistic program of social sciences (SPSS18) with the use of a set of statistical tools including: cronbach,s alpha coefficient, pearson correlation coefficient , correlation coefficient spearman،s,and the correlation coefficient Pearson,Mannwhitney test,ka² test, the study materialized the following results: 1.the level of psychological stress among nuses was medium level. 2.maritaladjustment among nuses was high level. 3.There are statistical significant differences in the level of psychological stress amongnuses attributed to each of the Expience, this is for thebenefit of(from 5years and overact(. 4.There are statistical significant differences in the level of psychological stress amongnuses attributed to each of the geographical location. , this is for thebenefit of(workers who are away from the workplace(. 5.There are statistical significant differences in the level of psychological stress amongnuses attributed to each of the work suite; this is for thebenefit of(workers in the children,s department(. 6.There are no statistical significant differences in marital adjustment level among nurses.due to the variables of study were attributed to (geographical location and work suite and Expience) 7. There are no correlation betweenpsychological stress and marital adjustment among nurses.. هدفت الدّراسة الحالية إلى التّعرف على ما إذا كانت هناك علاقة ارتباطية دالة إحصائيا بين الضّغوط النّفسية والتّوافق الزّواجي لدى الممرضات العاملات بمستشفيات مدينة المسيلة، وكذا التعرف على مستوى كل من الضّغوط النّفسية والتّوافق الزّواجي، بالإضافة إلى التعرف على ما إذا كان هناك فروق دالة إحصائيا في متغيري الدّراسة تعزى لـ ( الموقع الجغرافي وجناح العملوالخبرة).وللوصول إلى أهداف الدّراسة تمّ الاعتماد على المنهج الوصفي، واختيار عينة عشوائية بسيطة مقدرة ب 79 ممرضة أي ما يعادل 25% من مجتمع الدّراسة. وقصد جمع البيانات قامت الباحثة بتصميم استبيانين الأول حول الضغوط النفسية والآخر حول التوافق الزواجي والتّأكد من صدقهما وثباتهما، وتمّت معالجة البيانات المتحصل عليها من الأداتين بواسطة البرنامج الاحصائي (SPSS) حيث تم استخدام مجموعة من الأدوات الإحصائية منها: معامل ألفا كرونباخ،ومعامل الارتباط بيرسون، ومعامل الارتباط سبيرمان، واختبارمان ويتني، اختبار كا²، توصلت الدراسة إلى النتائج التالية: - مستوى الضّغوط النّفسية لدى الممرّضات متوسط. - مستوى التّوافق الزّواجي لدىالممرّضاتمرتفع جدا. - توجد فروق ذات دلالة إحصائيّة في مستوى الضّغوط النّفسية لدى الممرّضات تعزى لمتغيّرالخبرة وذلك لصالح (من 5سنوات فأكثر). - توجد فروق ذات دلالة إحصائيّة في مستوى الضّغوط النّفسية لدى الممرّضات تعزى لمتغير الموقع الجغرافي وذلك لصالح (البعيدات عن مقرّ العمل). - توجد فروق ذات دلالة إحصائيّة في مستوى الضّغوط النّفسية لدى الممرّضات تعزى لمتغير (جناح العمل) وذلك لصالح (العاملات بقسم الأطفال). - لاتوجد فروق ذات دلالة إحصائيّة في مستوى التّوافق الزّواجي عند الممرّضات تعزى لمتغيرات الدّراسة (الموقع الجغرافي- جناح العمل- الخبرة). - لا توجد علاقة ارتباطية ذات دلالة احصائية بين الضغوط النفسية والتوافق الزواجي لدى الممرضات بمدينة المسيلة. L'étude actuelle a visé de connaitre s'il y avait une relation significative entre les pressions psychiques et la convenance conjugale chez les infirmieres ,ainsi la connaissance de niveau des pressions psychiques et la convenance conjugale ajoutant de connaitre s'il y a des différences significatives dans les critères des études dus à la localisation géographique et la Département de travail ,l'expérience . Pour atteindre l'objectif de l'étude on s'est appuyé sur la manière descriptive et le choix d'un simple échantillon aléatoire de 79 infirmieres ce qui vaut 25% de la société étudiée on s'est appuyé ainsi sur le critère et sur le critère de pressions suite à la confirmation de leur honnêteté et de leur fiabilité et on a traité les données eus des deux outils par le programme de recensement "spss18" ou on a usé un ensemble d'outils de recensement comme : les médiateurs et la variance t_test ,coefficient de liaison Berson ,l'étude a abouti à: 1-Le niveau des pressions psychique chez les infirmieres est moyen. 2-Le niveau de convenance conjugale chez les infirmieres est trés haute. 3-Il y a de différences significatives au niveau des pressions psychiques chez les infirmieres dues au deux critères de l'étude "localisation géographique et spécialité" 4_Il y a de différences significatives au niveau des pressions psychiques chez les infirmieres dues au deux critères de l'étude "localisation géographique et spécialité 5_Il y a de différences significatives au niveau des pressions psychiques chez les infirmieres dues au deux critères de l'étude "localisation géographique et spécialité 6-Il n'y a pas de différences significatives dans le niveau de convenance conjugale chez les infirmieres dues aux critères de l'étude " localisation géographique et spécialité" 7-Il n'y a pas une relation négative avec une signification de recensement entre les pressions psychiques et la convenance conjugale chez les infirmieres dus à la localisation( géographique et la Département de travail ,l'expérience ).
Keywords: les pressions psychiques , la convenance conjugale , les infirmiere psychological stresses , marital adjustment , nurses. :الضّغوط النّفسيّة ، التّوافق الزّواجي،الممرّضات.